The importance of economic reform Policies in Arab states programs development: Case study of Sudanese economy - Sudan - Mohamed, Mahdi Abdallah (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aims to identify the causes of deterioration of the economy in Sudan, the problem of the study there is administration corruption, no separation of government authorities and the failure of economic policies, no transparency. The study was conducted (inductive, deductive and analysis) approach so most important results of the researcher: the lack of transparency, the immigration qualified outside Sudan and economic blockade are the reasons of the failure of the Sudanese economy. The most important recommendation of the study: to make real policies towards the motivating expatriates and investors, attention to agricultural, animal’s productions and transformative industries.